CATFISH DRYING (Clarias Batraclus) USING ‘TEKO BERSAYAP’ SOLAR DRYER - Yuwana Yuwana (BPFP Faperta UNIB, 2012)
Experiment on catfish drying employing ‘Teko Bersayap’ solar dryer was conducted. The result of the experiment indicated that the dryer was able to increase ambient temperature up to 44% and decrease ambient relative humidity up to 103%. Fish drying process followed equations : KAu = 74,94 e-0,03t for unsplitted fish and KAb = 79,25 e-0,09t for splitted fish, where KAu = moisture content of unsplitted fish (%), KAb = moisture content of splitted fish (%), t = drying time. Drying of unsplitted fish finished in 43.995 hours while drying of split fish completed in 15.29 hours. Splitting the fish increased 2,877 times drying rate.